The results of the 1984-85 winter raptor survey of Westfield Township, Fayette County, Iowa - Wehde, David D.et al (1984)
The report details the observation of raptors and shrikes in Westfield Township during the winter of 1984-1985. It includes details about species, weather, habitat, times of observation, bird sex, plumage, age, and behavior. The report includes tabular data and charts. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly Report of spring 1985. Epson - sheet feed